If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 5)(x + 5) + (y + -3)(y + -3) = 25 Reorder the terms: (5 + x)(x + 5) + (y + -3)(y + -3) = 25 Reorder the terms: (5 + x)(5 + x) + (y + -3)(y + -3) = 25 Multiply (5 + x) * (5 + x) (5(5 + x) + x(5 + x)) + (y + -3)(y + -3) = 25 ((5 * 5 + x * 5) + x(5 + x)) + (y + -3)(y + -3) = 25 ((25 + 5x) + x(5 + x)) + (y + -3)(y + -3) = 25 (25 + 5x + (5 * x + x * x)) + (y + -3)(y + -3) = 25 (25 + 5x + (5x + x2)) + (y + -3)(y + -3) = 25 Combine like terms: 5x + 5x = 10x (25 + 10x + x2) + (y + -3)(y + -3) = 25 Reorder the terms: 25 + 10x + x2 + (-3 + y)(y + -3) = 25 Reorder the terms: 25 + 10x + x2 + (-3 + y)(-3 + y) = 25 Multiply (-3 + y) * (-3 + y) 25 + 10x + x2 + (-3(-3 + y) + y(-3 + y)) = 25 25 + 10x + x2 + ((-3 * -3 + y * -3) + y(-3 + y)) = 25 25 + 10x + x2 + ((9 + -3y) + y(-3 + y)) = 25 25 + 10x + x2 + (9 + -3y + (-3 * y + y * y)) = 25 25 + 10x + x2 + (9 + -3y + (-3y + y2)) = 25 Combine like terms: -3y + -3y = -6y 25 + 10x + x2 + (9 + -6y + y2) = 25 Reorder the terms: 25 + 9 + 10x + x2 + -6y + y2 = 25 Combine like terms: 25 + 9 = 34 34 + 10x + x2 + -6y + y2 = 25 Solving 34 + 10x + x2 + -6y + y2 = 25 Solving for variable 'x'. Reorder the terms: 34 + -25 + 10x + x2 + -6y + y2 = 25 + -25 Combine like terms: 34 + -25 = 9 9 + 10x + x2 + -6y + y2 = 25 + -25 Combine like terms: 25 + -25 = 0 9 + 10x + x2 + -6y + y2 = 0 The solution to this equation could not be determined.
| 5n/2-5/7=95/14 | | 1/5y-7=-3/5-7/3 | | 7-wx=vx+3 | | 2/3-5/2y=-2/7 | | 5x/8-3=22 | | -3/2=-5/2x-7/3 | | 4/7y-3/2=-7/5 | | 5x+(x-8.4)=249.38 | | 8x^2=5(x-2) | | 5/3-9/4y=-1/2 | | 3w+10=6w-11 | | (200x-5000)/200x=.3 | | Ln(x+1)-2Ln(x)=0 | | 60=17+d | | log(x+2)=-log(12) | | f(x)=3sinx+4 | | 65-.2=35 | | 9(c-3)+9=5+c-23 | | q^2-2.67q-60=0 | | 5t+1=9 | | 7y-1=13 | | 6v^7-33v^6-18v^5=0 | | -5(-x-2)-3x=2x-12 | | 19(14m+14)= | | 22=-5x+42 | | 4x^3+6x^2+6x+2=0 | | (2h-5)(4h-3)= | | -7u^2-19u-10=0 | | -7(-3xy)= | | 3(2z-4+2)=5(-3z+2) | | 2k-5/-95 | | -6cos^2x+3senx+4=0 |